Government Budgetary Slack (Case Study at The Directorate General of Highways Ministry of Public Works and Housing) - Putra, Adestya Bismandoko Haryantono; Nurkholis, Nurkholis; Iqbal, Syaiful (Eduvest - Journal of Universal Studies, 2023)
The purpose of this study is to get an in-depth picture of how the practice of revenue budget gaps in the public sector can occur and the factors that drive it. This research uses qualitative research methods with a case study approach. Data collection was conducted through interviews and supported by documentation and direct observation, the informants involved in this study were managers responsible for the revenue budgeting process at each level. The practice of budget gaps is more aimed at avoiding the risk of not achieving the target, this is also because there is no reward and punishment system for achieving revenue targets. The results showed that pseudo-budget participation and information asympization triggered budget gaps. Factors The lack of strict supervision in the budgeting process and access to stagnant information make the budget gap continue to occur. The risk of this gap practice is that the organization does not know the true optimal potential and the loss of potential income from asset utilization.